Lime Burning in Clamp Kilns in Scotland's Western Central Belt: Primitive Industry or Simple but Perfectly Adequate Technology?. (2nd January 2017) - Bishop, Paul; Cuenca-Garcia, Carmen; Jones, Richard; Cook, Duncan
Abstract : Lime is a fundamental component in many industrial, agricultural and chemical processes, and is itself produced by an industrial process, namely, the heating in kilns (calcining, or more colloquially 'burning') of calcium carbonate rock or other carbonate material. Research and literature on lime burning in Scotland, based largely on lime production in Scotland's eastern Central Belt, are dominated by the view that lime burning in draw kilns is the paradigm for Scottish lime production. Other parts of Scotland, however, largely or completely ignored, draw kilns in favour of simpler clamp kilns, even in major industrial sites of lime production. This paper reports our map- and field-based surveys in Scotland's western Central Belt, which clearly point to the enduring importance and almost exclusive use of clamp kilns in that area's historical lime-burning industry.